1997
DOI: 10.1023/a:1005378527077
|View full text |Cite
|
Sign up to set email alerts
|

The association between haematological manifestation and mtDNA deletions in Pearson syndrome

Abstract: We studied the proportion of deleted mitochondrial DNA in blood cells from patients with Pearson syndrome. Patient 1 is a 17-year-old female with Kearns-Sayre syndrome who survived Pearson syndrome. Patient 2 is a 5-year-old boy with Pearson syndrome who recovered from refractory anaemia but continues to have thrombocytopenia and neutropenia. Patient 3 is a female neonate who died with severe acidosis and pancytopenia at 14 days of age. Southern blot analysis was performed with total DNA from three patients' b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…For mtDNA analysis, total DNA was extracted from muscle specimens of 6 patients (patients 1–6) and lymphocytes of patients 7 and 8. Southern blot and long polymerase chain reaction (PCR) analyses were performed to detect mtDNA rearrangements, as described previously 22, 23. Total mtDNA sequencing was performed as described previously 24.…”
Section: Methodsmentioning
confidence: 99%
“…For mtDNA analysis, total DNA was extracted from muscle specimens of 6 patients (patients 1–6) and lymphocytes of patients 7 and 8. Southern blot and long polymerase chain reaction (PCR) analyses were performed to detect mtDNA rearrangements, as described previously 22, 23. Total mtDNA sequencing was performed as described previously 24.…”
Section: Methodsmentioning
confidence: 99%
“…PS is characterized by iron-refractory, transfusion-dependent sideroblastic anemia, aplastic anemia [20], megaloblastic anemia, leukopenia, neutropenia, thrombocytopenia, or pancytopenia and exocrine pancreatic dysfunction (table 4) [21,22,23]. Additional clinical features include failure to thrive, villous atrophy with chronic diarrhea, lactic acidosis, muscle hypotonia, pancreas dysfunction, and ataxia [23, 24].…”
Section: Syndromic Mids With Hematological Manifestationsmentioning
confidence: 99%
“…Different phenotypic expression of the common deletion in relatives may be due to developmentally regulated tissue-specific nuclear factors [29]. There are indications that the blood cell count decreases with an increasing percentage of mutant mtDNA [21]. Conversely, it has been shown that the proportion of deleted mtDNA in bone marrow cells decreased as anemia improved [21].…”
Section: Syndromic Mids With Hematological Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty percent of affected children die in infancy because of bone marrow (BM) failure, infections, metabolic acidosis, or kidney insufficiency. In children who survive, a spontaneous hematologic improvement is noted in almost all cases, and in one of three cases a phenotypic transformation to Kearns–Sayre syndrome or Leigh syndrome is observed later in life . The presence of vacuolization in myeloid and erythroid progenitors on BM aspirate (BMA) is suggestive of PS.…”
Section: Introductionmentioning
confidence: 99%